The mediating influence of service failure explanation on customer repurchase intention through customers satisfaction - Tarofder, Arun Kumar; Nikhashemi, Seyedrajab *; Azam, Ferdous S. M.; Selvantharan, Prashantini; Haque, Ahasanul (Emerald, 2016)
Purpose The purpose of this paper is to examine the effect of explanation on customer satisfaction in the service failure stage. It seeks to better understand the dynamics of consumer repurchase intention through a mediating effect of customer satisfaction.